2019
DOI: 10.1103/physrevapplied.12.064055
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Hologram Enhanced Phased Arrays for Ultrasonic Particle Manipulation

Abstract: The ability to shape ultrasound fields is important for particle manipulation, medical therapeutics, and imaging applications. If the amplitude and/or phase is spatially varied across the wave front, then it is possible to project "acoustic images." When attempting to form an arbitrary desired static sound field, acoustic holograms are superior to phased arrays due to their significantly higher phase fidelity. However, they lack the dynamic flexibility of phased arrays. Here, we demonstrate how to combine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 32 publications
(38 reference statements)
0
29
0
Order By: Relevance
“…Recently, it has been demonstrated that static-phase plates, or holograms 8 , can modify an ultrasound field at high resolution with more than 10,000 pixels across the wavefront. This considerably increases the complexity of the projected static ultrasound fields, which has enabled first demonstrations of acoustic fabrication 9 and the assembly of cells 10 into designed patterns, beam steering 11 , and the compensation of wavefront aberration in transcranial focusing of ultrasound 12 . The ability to dynamically update and adjust these complex ultrasound fields with the aid of a high-resolution spatial ultrasound modulator (SUM), would present a major advance for these and related applications, which include medical imaging deep inside the body 13 , 14 , nondestructive testing of opaque solids 15 , the manipulation of submicron particles 16 , 17 , biological cells 18 , 19 , and even centimeter-sized objects 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that static-phase plates, or holograms 8 , can modify an ultrasound field at high resolution with more than 10,000 pixels across the wavefront. This considerably increases the complexity of the projected static ultrasound fields, which has enabled first demonstrations of acoustic fabrication 9 and the assembly of cells 10 into designed patterns, beam steering 11 , and the compensation of wavefront aberration in transcranial focusing of ultrasound 12 . The ability to dynamically update and adjust these complex ultrasound fields with the aid of a high-resolution spatial ultrasound modulator (SUM), would present a major advance for these and related applications, which include medical imaging deep inside the body 13 , 14 , nondestructive testing of opaque solids 15 , the manipulation of submicron particles 16 , 17 , biological cells 18 , 19 , and even centimeter-sized objects 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism of acoustofluidics uses acoustic waves to generate acoustic radiation forces on particles in the fluid; the strength of the acoustic radiation force depends on the size and density of the particle 12,[29][30][31][32][33] . The high biocompatibility of acoustofluidic devices also benefits downstream analysis by providing samples with complete structures and components [34][35][36][37][38] . Previously, we used acoustofluidics to separate bioparticles, including cells, bacteria, and platelets, in a highly biocompatible manner [39][40][41] .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the concept of holography has been applied to acoustic tweezers to levitate objects with twin, vortex, and bottle traps using single-sided arrays [ 21 ] and to dynamically manipulate multiple particles simultaneously and independently in a 3D space using a double-sided arrangement of two opposed arrays in the air [ 31 ]. Recently, particle manipulation which combines phased array and artificial acoustic structures has been proposed to integrate the advantages of the two methods [ 32 ].…”
Section: Introductionmentioning
confidence: 99%